Etiological Characterization of the Cutaneous Ulcer Syndrome in Papua New Guinea Using Shotgun Metagenomics. (16th June 2018) - Noguera-Julian, Marc; González-Beiras, Camila; Parera, Mariona; Ubals, Maria; Kapa, August; Paredes, Roger; Mitjà, Oriol
Abstract: Background: Treponema pallidum subsp pertenue and Haemophilus ducreyi are causative agents of cutaneous ulcer (CU) in yaws-endemic regions in the tropics. However, a significant proportion of CU patients remain polymerase chain reaction (PCR) negative for both bacterial agents. We aimed to identify potential additional etiological agents of CU in a yaws-endemic region. Methods: This population-based cohort study included children in Lihir Island (Papua New Guinea) examined during a yaws eradication campaign in October 2013–October 2014. All consenting patients with atraumatic exudative ulcers of >1 cm diameter were enrolled. Lesional swabs were collected for real-time PCR testing for T. pallidum subsp pertenue and H. ducreyi . We then performed shotgun whole DNA metagenomics sequencing on extracted DNA and taxonomically assigned shotgun sequences using a human microbiome reference. Results: Sequence data were available for 122 samples. Shotgun sequencing showed high classification agreement relative to PCR testing (area under the curve for T. pallidum/H. ducreyi was 0.92/0.85, respectively). Clustering analysis of shotgun data revealed compositional clusters where the dominant species (median relative abundance ranged from 32% to 66%) was H. ducreyi (23% of specimens), T. pallidum subsp pertenue (16%), Streptococcus dysgalactiae (12%), Arcanobacterium haemolyticum (8%), and Corynebacterium diphtheriae (8%). Sample clustering derived from ulcer microbial composition did not show geographical patterns. Conclusions: These data suggest a diverse etiology of skin ulcers in yaws-endemic areas, which may help design more accurate diagnostic tools and more effective antimicrobial treatment approaches to the cutaneous ulcer syndrome. Abstract : Streptococcus dysgalactiae, Arcanobacterium haemolyticum, and Corynebacterium diphtheriae, in addition to Treponema pallidum and Haemophilus ducreyi, are found in cutaneous ulcers from yaws-endemic areas, suggesting a polymicrobial origin of cutaneous ulcer syndrome in these areas.